2021
DOI: 10.3390/ma14020290
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Optical Methods for Zeta Potential Determination of Silica and Polystyrene Particles in Aqueous Suspensions

Abstract: Zeta potential is frequently used to examine the colloidal stability of particles and macromolecules in liquids. Recently, it has been suggested that zeta potential can also play an important role for grouping and read-across of nanoforms in a regulatory context. Although the measurement of zeta potential is well established, only little information is reported on key metrological principles such as validation and measurement uncertainties. This contribution presents the results of an in-house validation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Measurement uncertainties should be reported as combined uncertainties for the entire process. They can be derived from data obtained during a validation study; examples are available for measurements based on TEM (De Temmerman et al, 2014), DLS (Braun et al, 2011), PTA (Kestens et al, 2017;Ramaye et al, 2021), CLS (Antunez-Dominguez et al, 2020) or ELS (Ramaye et al, 2021). The measurement uncertainty associated to measurement results obtained during routine application of the validation method can be estimated as:…”
Section: 1mentioning
confidence: 99%
“…Measurement uncertainties should be reported as combined uncertainties for the entire process. They can be derived from data obtained during a validation study; examples are available for measurements based on TEM (De Temmerman et al, 2014), DLS (Braun et al, 2011), PTA (Kestens et al, 2017;Ramaye et al, 2021), CLS (Antunez-Dominguez et al, 2020) or ELS (Ramaye et al, 2021). The measurement uncertainty associated to measurement results obtained during routine application of the validation method can be estimated as:…”
Section: 1mentioning
confidence: 99%
“…SEM analysis has mostly revealed that the AgNPs formed in the literature were spherical, although a few authors reported irregular [ 184 ], triangular [ 185 ], hexagonal [ 129 ], isotropic [ 186 ], polyhedral [ 187 ], flake [ 188 ], flower [ 189 ], pentagonal [ 190 ], anisotropic [ 191 ], and rod-like structures [ 192 ]. Zeta potential values are used to confer colloidal stability to the integrated NPs, allowing the solution or dispersion to resist aggregation [ 193 ]. Scientists have employed macroalga Spirogyra varians to synthesize NPs with an average size of 35 nm in uniform and quasi-spherical shapes [ 37 ].…”
Section: Characterization Of Green Silver Nanoparticlesmentioning
confidence: 99%
“…Zeta potential (ZP) is used to investigate the surface charging behavior of a solid material in contact with an electrolyte solution and it gives information about the point of zero charge (pH pzc ) [ 34 ]. The main factor that affects the ZP is pH, and also there are other factors that affect the ZP including the ionic exchange, temperature, and viscosity of the medium [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main factor that affects the ZP is pH, and also there are other factors that affect the ZP including the ionic exchange, temperature, and viscosity of the medium [ 35 ]. ZP is indirectly measured through the following Henry's equation [ 34 ]: where μ is the average electrophoretic mobility of the particle, ε is the relative permittivity of the medium, z is the average zeta potential, η o is the dynamic viscosity of the medium, k is the reciprocal of the double layer thickness, and a is the radius of the spherical particle. The ratio of the particle radius to the electrical double layer thickness is given by the dimensionless parameter ka , which varies from 0 to ∞ [ 34 ].…”
Section: Resultsmentioning
confidence: 99%